Revolutionizing Cloud Modernization through AI Integration (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
This comprehensive research paper explores the transformative impact of Artificial Intelligence (AI) on cloud computing modernization. It examines the current state of cloud infrastructure, identifies key AI technologies driving innovation, and analyses strategies for AI-driven cloud modernization. The study investigates implementation approaches, presents case studies from major cloud providers, and discusses challenges and future trends. Through extensive analysis of recent developments and industry data, this research highlights the symbiotic relationship between AI and cloud computing, demonstrating how AI is revolutionizing cloud architectures, improving efficiency, enhancing security, and enabling new services. The paper concludes with an assessment of the economic impact and provides recommendations for businesses navigating this technological frontier.